The Twitter effect: The polics of tweeting during the 2018 Brazilian elections - Salles , Debora Gomes (2020)
In 2018, Jair Bolsonaro was elected Brazilian president amid accusations of benefiting from an industry of lies fired off on social media. As a far-right politician, his communication strategy was based on aggressive discourse, politically incorrect statements, discrediting the mainstream media and misleading information. Several studies have approached his Twitter campaign from a computational propaganda and disinformation perspectives, but questions remain about his overall communication strategy on the platform. Thus, the objective of this investigation is to critically and empirically analyze the uses and effects of Twitter related to the dissemination of political narratives, the agenda of the mainstream press, the framing of conversations and the formation of public opinion during the 2018 presidential campaign. Understanding the Twitter roles will allow us to provide a consistent analysis of how the platform was suitable for Bolsonaro's populist communication. We collected and examined more than 26 million tweets published during the elections, using different methodological approaches: observational analysis, content analysis, discourse analysis and social network analysis. Twitter, in addition to acting as a means for disaffected individuals to express themselves, also becomes the space in which users could gather and form partisan online crowds. During the Brazilian elections, Twitter's architecture allowed Bolsonaro to express himself without media intermediation and to embody the voice of the underdog and the unrepresented. In this sense, we argue that the use of Twitter by the extreme right succeeded because it was based on a populist logic of online communication.